ORGANIZATIONAL EFFICIENCY AND REDESIGNING ORGANIZATIONAL STRUCTURE IN TODAY’S COMPETITIVE: Life Sciences-Environment - Dr. Osman Saleh, Guest Editor (International Journal of Life Science and Pharma Research, 2016)
One of the most important needs of every organization is having the potentiality of rapid response to factors in increasingly environmental changes, and improving the efficiency of the organization in all horizontal. Today’s organizations should provide appropriate structures in order to overcome the shortcomings. Implementation of appropriate structures contribute to achieving organizational efficiency. Efficiency is a comprehensive and wide concept that includes all economic, political, social, and cultural sections. Managerial experience of developed countries shows that the most important factor in economic progress of organizations in those countries are programming, organizing, coordination, and a systematic movement towards increasing the organization efficiency. The final accomplishment of increasing the organizational efficiency is the amplification of competition in internal and external markets, development of market, increase of income, and a flourished economy. Regarding the importance of efficiency and its improvement in the organization, redesigning organizational structure is an important factor needs to be understood and studied by managers, business owners and practitioners.